Editor's Choice – Drug Coated Balloon Angioplasty vs. Standard Percutaneous Transluminal Angioplasty in Below the Knee Peripheral Arterial Disease: A Systematic Review and Meta-Analysis. (February 2020) - Ipema, Jetty; Huizing, Eline; Schreve, Michiel A.; de Vries, Jean-Paul P.M.; Ünlü, Çağdaş
Abstract : Objective: The aim was to review and analyse the literature on clinical outcomes of drug coated balloon (DCB) vs. standard percutaneous transluminal angioplasty (PTA) for the treatment of infrapopliteal arterial disease. Methods: This is a systematic review and meta-analysis. The MEDLINE, EMBASE and Cochrane Database of Systematic Reviews were searched for studies published between January 2008 and November 2018. Two authors independently performed the search, study selection, assessment of methodological quality and data extraction. Studies were eligible when reporting PTA and DCB outcomes in infrapopliteal arteries, published in English, human studies, and full text was available. Methodological quality was determined by MINORS and Cochrane risk of bias tool. GRADE methodology was used to rate the evidence for observed outcomes. The primary outcome was the 12 month limb salvage rate. Secondary outcomes were 12 month survival, amputation free survival (AFS), restenosis, and target lesion revascularisation (TLR) rates. Inclusion criteria for pooling data were randomised controlled trials and comparative studies with 12 month outcomes. Results: Ten studies representing 1593 patients met the inclusion criteria. The quality was assessed as moderate or low. Data from five studies were pooled, and 12 month outcomes for DCB vs. PTA were limb salvage rate, 94.0% vs. 95.7% (odds ratio (OR), 0.92; 95% confidence interval (CI), 0.39–2.21); and survival rate, 89.8% vs. 92.9% (OR 0.69; 95% CI 0.39–1.21). Data from four studies were pooled, and 12 month outcomes for PTA vs. DCB were restenosis rate, 62.0% vs. 32.9% (OR 2.87; 95% CI 0.83–9.92); and TLR rate, 27.8% vs. 14.0% (OR 2.76; 95% CI 0.90–8.48). Pooled data from two studies showed 12 month AFS rate for DCB vs. PTA; 82.5% vs. 88.7% (OR 0.79; 95% CI 0.23–2.75). No statistically significant differences were found. Conclusion: Based on this systematic review and meta-analysis no significant differences in limb salvage, survival, restenosis, TLR, and AFS rates were found when DCB angioplasty was compared with standard PTA.